2019
DOI: 10.1007/s11064-019-02735-2
|View full text |Cite
|
Sign up to set email alerts
|

Anticonvulsant Activity of Pterostilbene in Zebrafish and Mouse Acute Seizure Tests

Abstract: Pterostilbene (PTE), a natural dimethylated analog of resveratrol, possesses numerous health-beneficial properties. The ability of PTE to cross the blood–brain barrier raised the possibility that this compound may modulate central nervous system functions, including seizure activity. The aim of our study was to investigate the activity of PTE in the larval zebrafish pentylenetetrazole (PTZ) seizure assay and three acute seizure tests in mice, i.e., in the maximal electroshock seizure threshold (MEST), 6 Hz-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 45 publications
(55 reference statements)
0
40
0
Order By: Relevance
“…In order to detect epileptiform-like discharges in zebrafish larvae, the EEG recordings were conducted according to the method described previously [39].…”
Section: Eeg Analysismentioning
confidence: 99%
“…In order to detect epileptiform-like discharges in zebrafish larvae, the EEG recordings were conducted according to the method described previously [39].…”
Section: Eeg Analysismentioning
confidence: 99%
“…We found out that the preincubation of larval zebrafish with AS-1 decreased the number and cumulative duration of EEG discharges induced by acute PTZ. This proconvulsant in larval zebrafish induces a number of behavioral changes, starting with burst swimming and culminating in tonic-clonic convulsions, resembling epileptic seizures in mammals [34,63,64]. At the EEG level, exposure to PTZ induces frequent, recurrent ictal-like discharges [33,65].…”
Section: Discussionmentioning
confidence: 99%
“…At the EEG level, exposure to PTZ induces frequent, recurrent ictal-like discharges [33,65]. To date, the zebrafish PTZ assay has been validated and extensively characterized using commercially available AEDs [33,66], while obtained results have been proved to translate well to rodent models [34,65,67,68].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence has revealed that PTER could exert protective actions against the oxidative stress or inflammatory reaction in various types of neurons, such as neuronal SH-SY5Y cells and spinal cord neurons, as well as in ischemia-or hypoxia-induced brain injuries [14][15][16][17][18][19][20][21]. PTER and other resveratrol analogs were previously reported to exert antiepileptic actions [22][23][24] to decrease dopamine release in striatal slices, and to substantially ameliorate depressive or cognitive behavioral deficits in rats [25][26][27]. It is also noted that the presence of PTER could disrupt pituitary function [3,28].…”
Section: Introductionmentioning
confidence: 99%